2010
DOI: 10.1002/adfm.201000461
|View full text |Cite
|
Sign up to set email alerts
|

Galactose Encapsulated Multifunctional Nanoparticle for HepG2 Cell Internalization

Abstract: The fluorescent dye Cy3 and galactose derivatives are covalently assembled with different ratios on the surfaces of magnetic nanoparticles (MNPs) to produce multifunctional HepG2 cancer cell–targeting agents and the effect of ligand spatial orientation on the MNP surface is investigated on targeting specificity. By using a mixture of bis‐N‐hydroxysuccinimide ester (a bifunctional linker) and OSu‐activated Cy3 (w/w = 30:1), stable and quantifiable fluorescent MNPs (Cy3@MNPs) are synthesized that could be subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 55 publications
3
89
0
Order By: Relevance
“…In most cases, particles with diameter size less than 120 nm were reported to be well suited for localised drug delivery applications due to the fact that they can be synthesised on a large scale with high monodispersed with almost no drug loss to the malignant sites. This point has previously been made by several authors [33,34] that the localisation behaviour of Ag particles within the malignant areas is dependent on the size as their direction can be sterically hindered in cellular matrix due to the mucoadhesives of encapsulated chemotherapeutic substances [35]. The particle size of conjugate Ag particles along with their morphology does indeed give better surface chemistry effect which arises the opsonisation behaviour.…”
Section: Nanoscale Silver Particlesmentioning
confidence: 76%
“…In most cases, particles with diameter size less than 120 nm were reported to be well suited for localised drug delivery applications due to the fact that they can be synthesised on a large scale with high monodispersed with almost no drug loss to the malignant sites. This point has previously been made by several authors [33,34] that the localisation behaviour of Ag particles within the malignant areas is dependent on the size as their direction can be sterically hindered in cellular matrix due to the mucoadhesives of encapsulated chemotherapeutic substances [35]. The particle size of conjugate Ag particles along with their morphology does indeed give better surface chemistry effect which arises the opsonisation behaviour.…”
Section: Nanoscale Silver Particlesmentioning
confidence: 76%
“…For example, Lai et al [39] synthesized HepG2 cancer cell targeting glycoMNPs incorporating a fluorescent dye (Cy3) and galactosyl derivatives of different valence (triantennary 1a, 1b and monoantennary 2a) and length (resulting in different ligand spatial presentation on the MNP surface). The ligands were attached to the aminofunctionalized MNPs by bis(N-hydroxysuccinimide) chemistry (Fig.…”
Section: Covalent Functionalization With Carbohydratesmentioning
confidence: 99%
“…For instance, Lai et al [39] reported the synthesis of 10-nm MNPs functionalized with a fluorescent dye and monoantennary or triantennary galactosyl ligands to selectively target liver cancer cells (HepG2) in vitro. These galactose residues can specifically interact with the extracellular ASGP-R, which is abundantly present in HepG2 cells, thus triggering the uptake of glycoMNPs into the cell.…”
Section: Cell Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that polyethylene glycol plays a role of increasing the residence time of MSNs in the systemic circulation, while D-Galactosamine enriches the MSNs in HepG2 cell line 3 . The antitumor drug; doxorubicin was encapsulated in the internal surface of MSNs, whereas, polyethylene glycol-galactose was grafted onto the external surface of MSNs and the loaded doxorubicin showed a pH-responsive release profile and higher cytotoxicity against the HepG2 cell line by MTT measurements, which is a highly desirable characteristic for tumortargeted drug delivery 4 .…”
mentioning
confidence: 99%